Manipulation of Pattern of Cell Differentiation in a hetR Mutant of Anabaena sp. PCC 7120 by Overexpressing hetZ Alone or with hetP - He Zhang; Xudong Xu (Life, 2018)
In the filamentous cyanobacterium, Anabaena sp. PCC 7120, single heterocysts differentiate at semi-regular intervals in response to nitrogen stepdown. HetR is a principal regulator of heterocyst differentiation, and hetP and hetZ are two genes that are regulated directly by HetR. In a hetR mutant generated from the IHB (Institute of Hydrobiology) substrain of PCC 7120, heterocyst formation can be restored by moderate expression of hetZ and hetP. The resulting heterocysts are located at terminal positions. We used a tandem promoter, PrbcLPpetE, to express hetZ and hetP strongly in the hetR mutant. Co-expression of hetZ and hetP enabled the hetR mutant to form multiple contiguous heterocysts at both terminal and intercalary positions. Expression of hetZ, alone resulted in terminally located heterocysts, whereas expression of hetP, alone produced enlarged cells in strings. In the absence of HetR, formation of heterocysts was insensitive to the peptide inhibitor, RGSGR.